Fondasi Realisme Ibn Sīnā dalam Metafisika Kitāb al-Syifā’ - M F Attar (ILMU USHULUDDIN, 2015)
This paper is a translation and commentary on the first chapter of Book V of the Metaphysics of Avicenna’s (d. 1037) major philosophical work, the Shifāʾ. In this particular section of this work and the rest of the chapters of Book V, Avicenna lays out the metaphysical foundations to his realist epistemology. One central doctrine that he develops in the first chapter is the idea that a thing’s essence is distinct from its existence. By existence, Avicenna includes concrete existence in the outside realm and also conceptual existence in the mind (i.e. the way things are said or structured in concepts.) A thing’s essence has a neutral ontological position, neither primarily outside nor primarily conceptual, though it can exist as a concrete thing and/or as a concept. The fact that the mind and the concrete world may share a common object is the basis of Avicennian realist epistemology: this is how our thoughts and impressions about the world actually correspond to the world.